Carrier recombination at defects in silicon: The effect of transition metals and hydrogen passivation - Wilshaw, P; Blood, A; Braban, C (1997)
Results are presented of the EBIC contrast and hence recombination efficiency of a large variety of extended defects. It is shown that the recombination behaviour can be split into three categories associated with strong, medium and weak contrast defects respectively and that this behaviour can be explained in terms of the position of the defect states in the band gap. It is shown that hydrogen passivation is extremely successful at removing deep levels in the band gap, even when these are associated with precipitates, but that it has little effect on shallow levels.